PROPOSING BILATERAL INTEGRATION OF TRADITIONAL AND CONVENTIONAL MEDICAL EDUCATION AND PRACTICE PERCEIVING MAHAMANA MALAVIYAS VISION - Misra, Sanchit (International Journal of Ayurveda and Pharma Research, 2015)
Total 69% of Allopathic doctors prescribe branded Ayurvedic preparations. In a study in North India, it has been observed that, the prescriptions of Allopathic doctors contained 88% allopathic and 12% Ayurvedic drugs. Another study reported that Ayurvedic drugs were prescribed by 5.26% of allopathic-practitioners. Hence, even without formal knowledge and training, allopathic physicians do not want to refer patients to Ayurvedic doctors but prefer to prescribe Ayurvedic drugs on their own to the patients. This tendency of allopathic doctors is unethical and unwarranted. Similar cross prescriptions are also common among Ayurvedic doctors who frequently prescribe modern drugs, but they are given formal allopathic training during their UG and PG education, which may justify their prescription of Allopathic drugs to some extent. Thus, it is obvious that how important it is for Allopathic practitioners to learn the basics of Ayurveda as its demand is increasing and as it is a fact that the practice of Complementary Ayurveda by Allopathic practitioners is also as important as practice of Complementary Allopathy is by Ayurvedic practitioners for a successful practice. Thus Bilateral Integration of both streams of Medicine in India has now become essential for sustaining the ethical practice with legal provisions in public interest.